Možnosti uporabe sistema gozdnih rastiščnih tipov za opredelitev habitatnih tipov (Natura 2000) - Kutnar, Lado (Gozdarski vestnik, 2013)
Forest-management planning involves more and more items related to nature conservation which is also provided by the relevant legal acts. Although the nature conservation concern is primarily focused to the habitat types and species within the European ecological network of Natura 2000 areas, in the concept of sustainable forest management attention needs to be paid to the forest habitat types (Habitat Directive, 1992) on their entire area. In the analysis, we found that, mainly due to objective circumstances, some forest and scrubland habitat types have not been adequately addressed in the forest management planning system so far. In this paper we have demonstrated the possibility of using more recent Typology of Slovenia forest sites (2012) for conservation purposes. Possibilities of classification in the appropriate habitat type were shown for each site type described on the basis of ecological and floristic similarity of the related forest plant communities. We encountered a degree of uncertainty in classification of forests in the habitat type 9410 Acidophilous Picea forests of the montane to alpine levels (Vaccinio-Piceetea) and the habitat type 9110 Luzulo-Fagetum beech forests. Although the nature fir forests have considerable nature conservation importance, they were not adequately integrated into the existing concept of nature conservation. Therefore, we propose to describe the fir forests in Slovenia and to take measures for their nature-conservation treatment.
Keywords: rastiščni tipi; habitatni tipi; Natura 2000; klasifikacija; gozdnogospodarsko načrtovanje; naravovarstvo; Slovenia; Slovenija